Interlab Cell Line Collection: Bioresource of Established Human and Animal Cell Lines. (19th June 2015) - Parodi, Barbara; Aresu, Ottavia; Visconti, Paola; Manniello, Maria Assunta; Strada, Paolo
The Interlab Cell Line Collection (ICLC) was established in 1994 as a core facility of the National Institute of Cancer Research. It supplies: human and animal cell lines; Short Tandem Repeat (STR) profiling of human cell lines; quality control service; mycoplasma detection and eradication service; safe deposit service and patent deposit service of cell lines and hybridomas. The catalogue of services is on-line, and the cell lines are distributed all over the world.